2016
DOI: 10.3171/2015.4.jns142415
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery for vestibular schwannomas: evaluation of tumor control and its predictors in a large patient cohort in The Netherlands

Abstract: OBJECT The authors of this study sought to assess tumor control and complication rates in a large cohort of patients who underwent Gamma Knife radiosurgery (GKRS) for vestibular schwannoma (VS) and to identify predictors of tumor control. METHODS The records of 420 patients treated with GKRS for VS with a median marginal dose of 11 Gy were retrospectively analyzed. Patients with neurofibromatosis Type 2 or who had undergone treatment for VS previously were excluded. The authors assessed tumor control and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 33 publications
2
47
0
3
Order By: Relevance
“…34 The difference between mutation types and therefore the proportion of both phenotypes might explain the difference in outcome of GKRS reported in the various published series. The view that a larger tumor volume is an independent factor associated with shortened PFS is supported by multivariate analysis done by Klijn et al 14…”
Section: Discussion Tumor Control After Gkrs In Nf2mentioning
confidence: 85%
See 1 more Smart Citation
“…34 The difference between mutation types and therefore the proportion of both phenotypes might explain the difference in outcome of GKRS reported in the various published series. The view that a larger tumor volume is an independent factor associated with shortened PFS is supported by multivariate analysis done by Klijn et al 14…”
Section: Discussion Tumor Control After Gkrs In Nf2mentioning
confidence: 85%
“…15 Current available studies on Gamma Knife radiosurgery (GKRS) for sporadic VS are abundant and show excellent results for tumor control and adverse effects. 14,16,21,25 For NF2-related VS, the number of studies is limited, and the studies show varying tumor control rates. 17,18,20,24,29,30,35,36 Consequently, the use of radiosurgery as a first-line treatment option is controversial.…”
mentioning
confidence: 99%
“…Vertigo or gait disturbance was reported in up to 1.1% of patients, with a higher prevalence in the lower dose cohort, which also applied to tinnitus (occurring in 0.1%). In another recent study that provided data over a large cohort of 420 cases that were treated by GKS in the Netherlands, 9 the authors reported that 1% of patients had new or increased permanent facial weakness, 3.1% of patients reported trigeminal neuropathy, 1.2% of patients had new or increased hydrocephalus, up to 13.2% of patients reported tinnitus, and 14.8% of patients reported new or increased vertigo. In the same study, serviceable hearing was preserved in 60.6% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important VS are hypo-to isointense or isointense when compared to brain parenchyma on T1-weighted images [54][55][56]. Tumoral cysts are hypointense in comparison to the brain parenchyma on T1-weighted images [54,57]. The T1-weighted images can visualize intratumoral hemorrhage as an isointense or hyperintense area [58,59].…”
Section: Sporadic Vsmentioning
confidence: 99%